2017
DOI: 10.1038/s41598-017-10634-1
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic interaction between jasmonic acid and cytokinin in xylem development

Abstract: Developmental flexibility under stress conditions largely relies on the interactions between hormones that mediate stress responses and developmental processes. In this study, we showed that the stress hormone jasmonic acid (JA) induces formation of extra xylem in the roots of wild-type Arabidopsis thaliana (Col-0). JA signaling mutants such as coronatine insensitive1-1 and jasmonate resistant1-1 did not form extra xylem in response to JA, but the JA biosynthesis mutant oxophytodienoate-reductase3 did form ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 59 publications
3
74
0
Order By: Relevance
“…Also, based on ChIP data, it appears that in the absence of cytokinin some other regulatory component, that might work downstream of MYC2, is involved in the regulation of ARR16 . Similar observation has also been made by Jang et al, .…”
Section: Discussionsupporting
confidence: 91%
“…Also, based on ChIP data, it appears that in the absence of cytokinin some other regulatory component, that might work downstream of MYC2, is involved in the regulation of ARR16 . Similar observation has also been made by Jang et al, .…”
Section: Discussionsupporting
confidence: 91%
“…The interactive influence of cytokinin may substantiate JAs negative impact to promote plant survival under extreme saline conditions. The synergistic interaction between zeatin and JAs may also enhance the salt induced-vasculature in roots to enhance water uptake, which is also supported by the well maintained RRWC in roots of treated plants (Supplementary Figure 2D) (Ueda Kato, 1982; Nitschke et al, 2016; Jang et al, 2017).…”
Section: Discussionmentioning
confidence: 60%
“…Many studies reported that developmental flexibility under stress conditions largely depends on the interplay between stress-related hormones and growth-related hormones, and increasing evidence indicates that JA and GA antagonistically interact to coordinate plant growth and defense [50][51][52]. Extensive studies on the JAZ JA signaling repressor proteins, and the DELLA GA signaling repressor proteins revealed that direct interaction between JAZs and DELLAs mediates the antagonistic interaction between JA and GA ( Figure 1) [27,28].…”
Section: The Ja-ga Interaction and Its Underlying Molecular Mechanismmentioning
confidence: 99%
“…The AHPs activated by phosphorylation move into the nucleus and sequentially activate B-type ARABIDOPSIS RESPONSE REGULATOR (ARR) transcription factors responsible for the transcription of cytokinin-responsive genes [69,70]. Genes encoding components of the cytokinin signaling pathways, such as AHKs, AHPs, and ARRs, are affected by JA or environmental stresses such as drought, salt, and cold, suggesting that the cytokinin response is involved in plant stress responses [50,56,71,72].…”
Section: Cytokinin Metabolism and Signalingmentioning
confidence: 99%
See 1 more Smart Citation